Channel migration characteristics of the Yamuna River from 1954 to 2015 in the vicinity of Agra, India: A case study using remote sensing and GIS. Issue 3 (3rd July 2019) - Ali, P. Yunus; Jie, Dou; Khan, Armugha; Sravanthi, N.; Rao, Liaqat A. K.; Hao, Chen
ABSTRACT: The flood plain management in any area requires identification of the zones of river migration, and regulate the development within these areas. This study evaluates the river migration behaviour and quantifies the adjustment on an alluvial reach of the Yamuna River through an analysis of topographic map and satellite imageries for the period between 1954 and 2015. The Digital Shoreline Analysis System (DSAS) tool in a geographic information system (GIS) is used to quantify the river migration: (i) net river migration; (ii) linear regression rate, and (iii) end point rate is calculated for ∼70 km length of stream reach by casting 1580 transects at 50 m intervals. The results show that the River Yamuna at the study reach of meandering bend 5 has adjusted to the effects of the flood in the 1970's. However, the decline in river discharge rate over the last couple of decades reduces the erosional capacity of the river and subsequent migratory behaviour. Sinuosity indices indicate that the river has both increased and decreased in length after 1954. Our result shows that the DSAS method has the potential for assessing and quantifying past and potential future channel migration, and then define the migration boundaries.